THE HISTORY OF ASSESSING THE IMPACT OF US DOLLAR EXCHANGE RATE FLUCTUATIONS ON THE NATIONAL CURRENCY MARKET (Web of Discoveries: Journal of Analysis and Inventions, 2026)
This article analyzes the history of the impact of the US dollar exchange rate on the national currency market. The research examines the influence of exchange rate fluctuations on economic stability, historical changes, and their consequences. The formation period of the currency market of Uzbekistan and the issues of reducing the level of dollarization are highlighted.